A recent history of homicide investigation: changes and implications for criminal justice in England and Wales - Pike, Sophie (Routledge contemporary issues in criminal justice and procedure, 2023)
"Drawing on in-depth research, including interviews with former and serving detectives, this book explores how homicide investigation in England and Wales has changed since the 1980s, and the opportunities and challenges that have arisen as a consequence. The investigation of homicide in England and Wales became subject to significant reform in the 1980s, when the inquiry into the Yorkshire Ripper investigation identified numerous failings in how the hunt for Peter Sutcliffe was conducted. These investigations have been subject to criticism and change from that moment onwards. This book explores how change has shaped every facet of these investigations, with four main areas identified: science and technology; legislation, regulation and guidance; investigative practice; and, lastly, detective status and culture. The work shows that change has been the result of four primary catalysts: a growing preoccupation with risk; the changing political landscape; reactions to miscarriages of justice and other cases; and advances in science and technology. What has been lost and gained as a result of change is also explored. It has, in many ways, been positive, as scientific and technological advances allow investigators to plot an offender's movements and draw a clearer picture of what transpired. However, change has created today's more risk-averse homicide detectives who must manage the vast amounts of technological information that modern-day investigations now generate. They must also contend with a raft of legislation and guidance that now govern investigations, and budget pressures not faced by their predecessors. The book will be a valuable resource for students, researchers and policy-makers in the areas of Criminal Law and Procedure, Criminal Justice, Criminology, and Policing"--